A distributional analysis of the public-private wage differential in India - Mehtabul Azam; Nishith Prakash (Institute for the Study of Labor (IZA), 2010)
We investigate the public-private wage differential in India using nationally representative micro data. While the existing literature focuses on average wage differential, we study the differences in the wage distributions. The raw wage differential between public and private sector is positive across the entire distribution for both genders irrespective of area of residence. A quantile regression based decomposition analysis reveals that the differences in observed characteristics (covariate effect) account for only a small part of the wage differential at lower quantiles, but a larger part at higher quantiles. At the very top of the distribution, covariate effect account for a majority of the observed wage differential.
urn:nbn:de:101:1-201010133121
Keywords: J3; J45; 330; quantile regression; public-private wage differential; India